NORMA SUBYEKTIF DAN NIAT BERPENGARUH TERHADAP PERILAKU MEROKOK REMAJA DI YOGYAKARTA - Riyadi, Sujono (Jurnal Ilmiah Kesehatan Keperawatan, 2020)
ABSTRACTBackground: Smoking behavior is an act that is very detrimental to the health of the perpetrators and those around them. In cigarettes there are chemical substances that are very dangerous for one's health, both active smokers and passive smokers. The purpose of this study was to determine the effect of the non-smoking subjective norm and non-smoking intention on the smoking behavior of adolescents in Kulon Progo Yogyakarta.Subject and Method: This was a case control study conducted in Kulon Progo, Yogyakarta, from April to June 2018. A total of 400 adolescents consisiting of 200 smokers and 200 non smokers were selected for this study. The dependent variable was smoking behavior. The independent variables were intention and subjective norm. The data were collected by questionnaire and analyzed by a path analysis.Results: Â The decision not to smoke was associated with strong intention (b= 1.74; 95% CI= 2.29 to 1.18; p<0.001), favorable subjective norm (b= 1.58; 95% CI = 0.99 to 2.18; p<0.001)Conclusion: The decision not to smoke is associated with intention, subjective norm.Â Keywords: Smoke, Intention, Subjective norm.